Factors Associated with Standing Desk Use in the Workplace: Implications for Workplace Health Promotion Programs and Interventions - Amanda H. Wilkerson; Ny'Nika T. McFadden; Nuha Abutalib; Adriana Dragicevic; Shristi Bhochhibhoya; Bushra R. Salous (New Prairie Press, 2022)
The purpose of this study was to explore what sociodemographic, psychosocial, and behavioral factors were associated with standing desk use in the workplace among full-time non-instructional staff at a large, public university in the south-central United States. Data were collected using an online survey in Spring 2019 that contained items to assess sociodemographic variables, psychosocial factors, physical activity, and standing desk use. Participants (n = 381) were predominantly female (79.1%), white (91.7%), and 23.9% used a standing desk. In the binary logistic regression model, sedentary behavior awareness (OR = 1.11; 95% CI:1.04,1.18), self- efficacy (OR = 1.06; 95%CI:1.03,1.10), and salaried staff classification (OR = 1.99; 95%CI:1.19,3.34) were significantly associated with standing desk use (R2 = 0.16; p < .001). Findings from this study not only identify important psychosocial factors that may be targeted in future standing desk-based interventions but also highlight specific subgroups of employees that should be targeted in intervention recruitment.